Students’Learning Strategies in Developing Speaking Skills - Chelvia, Wilda; Sari, Heni Novita (IKIP Siliwangi, 2025)
One of the languages used for communication is English. Speaking fluently in English is one of the most important components. Learning to speak was another essential component of learning a new language. Students needed to choose the most effective learning strategy to help them got more knowledge and to develop their speaking skills. Therefore, this research was carried out to know the strategies of learning that were used to develop speaking skills by English Language Education students at Muhammadiyah university of Prof. Dr. Hamka. To collect the data, the writer used questionnaire as quantitative data. The results showed that there were six learning strategies used by students namely metacognitive strategies, compensatory strategies, cognitive strategies, affective strategies, memory strategies, and social strategies. Related to this, the most frequent strategies implemented by the students were metacognitive strateegies (80%), compensatory strategies (79.38%), and the cognitive strategies (78%).